Joint displays for mixed methods research in psychology. (December 2021) - McCrudden, Matthew T.; Marchand, Gwen; Schutz, Paul A.
Abstract: Mixed methods researchers use joint displays for integration at different phases of the research process in psychological research. Joint displays are visual displays that are used to integrate quantitative and qualitative data during data collection, analysis, and interpretation. We discuss different mixing purposes and how joint displays may help researchers integrate the quantitative and qualitative strands of a study. We provide examples of joint displays for data collection and for data analysis, including newer innovations. Finally, we discuss considerations, including benefits and challenges, of using joint displays during data collection and analysis.